A 3D titanate aerogel with cellulose as the adsorption-aggregator for highly efficient water purification. Issue 12 (2nd March 2017) - Xiong, Ye; Wang, Chao; Wang, Hanwei; Yao, Qiufang; Fan, Bitao; Chen, Yipeng; Sun, Qingfeng; Jin, Chunde; Xu, Xijin
Abstract : Making full use of the hydrophilicity, hydroxyl reactivity, high strength and stiffness, low weight and biodegradability of cellulose, a novel cellulose-based adsorption-aggregator is creatively exploited. Abstract : Making full use of the hydrophilicity, hydroxyl reactivity, high strength and stiffness, low weight and biodegradability of cellulose, a novel cellulose-based adsorption-aggregator is creatively exploited. In this work, a 3D titanate aerogel with cellulose as the adsorption-aggregator has been fabricated for highly efficient water purification. Herein, the polyhydric cellulose not only acts as a crosslinking agent, but also facilitates ion-induced aggregation, which strongly promotes the adsorption efficiency of the titanate and effectively improves its inherent shortcomings as an inorganic adsorbent. The Pb 2+, Sr 2+, Cu 2+, Ra 2+, and Cd 2+ adsorption capacities surprisingly reach 2.46, 1.43, 2.51, 1.22, and 1.98 mmol g −1, respectively. Moreover, it may be applied in the fields of water purification agents, oxidants, catalysts, disinfectants and photoelectrochemical components, in view of the hydroxyl oxidation, hydroxyl induction, disinfection, and water purification abilities of cellulose. Therefore, the development of cellulose adsorption-aggregating agents is both reasonable and of great value.